THE EFFECT OF OCCUPATIONAL HEALTH AND SAFETY (K3), COMMUNICATION AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE AT PT. PERKEBUNAN NUSANTARA III (PERSERO) MEDAN - Jonathan Rajagukguk; Krista Moldofa Nadeak; Zose Andreas Putra; Cut Fitri Rostina (SEAN Institute, 2022)
The purpose of this research to test and analyze the Effect ofOccupational Health and Safety (K3), Communication, andLeadership Style on employee performance at Pt. PerkebunanNusantara III Persero Medan. To support the performance ofemployees, the company provides several benefits such as salary,allowances, bonuses, THR, premium school children assistance,and BPJS. In the case of occupational health and safety, which hasbegun to become ineffective, the tools used, which makeemployees a little uncomfortable, indicate that there is still a lackof improvement in the equipment provided by the company. Incommunication, since the Covid 19 pandemic has causedemployees to have a little less communication because of (WFH).The leadership style is also the same due to the pandemic, whichmakes it a little difficult for leaders to supervise employees. Thisresearch was conducted at PT. Perkebunan Nusantara III, with atotal population of 538 people. This study uses a quantitativedescriptive method, the sampling technique used is randomsampling, to determine the number of samples, this study uses theSlovin formula, the number of samples obtained in this study were84 employees. Researchers used data collection by usingquestionnaires, interviews, documentation studies, Based on theresults (F-test) simultaneously showing the test results, obtainedthe value of Fcount (5.928) > Ftable (2.72) and significantprobability (0.001 <0.05), This means that the influence ofoccupational health and safety, communication, and leadershipstyle has a positive and significant effect on employeeperformance. Based on the results (T-test), the OccupationalHealth and Safety variable (2.412> 1.990) and significant (0.42<0.05) and the Communication variable (2.252> 1.990) andsignificant (0.027 < 0.05), and the Style variable Leadership(2.127>1.990) and significant (0.036 <0.05) means partiallypositive and significant effect on employee performance at PT.Perkebunan Nusantara III Persero Medan